Clinical characteristics of sarcoidosis patients in the United States versus China - Zhou, Ying; Lower, Elyse E.; Feng, Yinping; Du, Shanshan; Li, Huiping; Baughman, Robert P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Objective: To characterize and compare the disease manifestations between patients with sarcoidosis in China versus the United States using the World Association of Sarcoidosis and Other Granulomatous disease (WASOG) instrument. Methods: Clinical data and disease manifestations were reviewed from sarcoidosis patients from the Shanghai Pulmonary Hospital (China) and University of Cincinnati Medical Center (US). Results: 481 Chinese patients and 522 US patients with sarcoidosis were studied. Extra-pulmonary sarcoidosis was observed more frequently in US patients than Chinese patients. Chinese patients were more likely to develop hypercalcemia or hypercalcuria (23%) compared to US patients (14%) (χ2=18.342, P